CONCEPTS OF CULTURE, CIVILIZATION, VALUE THEORETICAL FOUNDATIONS OF LEARNING (Intent Research Scientific Journal, 2023)
We are living in the XXI st century, when the processes of globalization are rapidly developing, when civilizations, cultures, and values are converging, understanding each other, and competing with each other. The most important principles of the approach to this issue in the study of the concepts of culture and civilization values are comparatively analyzed and approached on a scientific and creative basis. In the philosophical understanding of culture, civilization and values, materialist, positivism, objective idealism and many other traditions related to philosophical reasoning are distinguished. In each of these, human nature and world of social group, physical, spiritual and spiritual life activities are studied in a unique analytical way.Strengthening intercivilizational dialogue, bringing cultures and values closer to each other, and harmonizing them are of great importance for the future of humanity. It is important to study them. Because it is known from history that at the root of many conflicts lies the culture of not being able to understand each other well, the incompatibility of values. In this regard, first of all, it is necessary to form a proper dialogue between civilizations, to realize the human factor as a supreme value. It is important to study these on the basis of appropriate sources.